2008
DOI: 10.1186/1471-2377-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide exposure and risk of Parkinson's disease: A family-based case-control study

Abstract: BackgroundPesticides and correlated lifestyle factors (e.g., exposure to well-water and farming) are repeatedly reported risk factors for Parkinson's disease (PD), but few family-based studies have examined these relationships.MethodsUsing 319 cases and 296 relative and other controls, associations of direct pesticide application, well-water consumption, and farming residences/occupations with PD were examined using generalized estimating equations while controlling for age-at-examination, sex, cigarette smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
176
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 252 publications
(205 citation statements)
references
References 39 publications
12
176
0
2
Order By: Relevance
“…Another population-based study also reported an increased risk with occupational exposure to herbicides (OR 3.06, 95% CI 1.34-7.00) [290]. A family-based study that found a dose-response relationship between overall pesticide exposure and PD reported an increased risk related to herbicides (OR 1.59, 95% CI 1.00-2.54) but could not examine dose-response [302].…”
Section: Case-control Studiesmentioning
confidence: 97%
See 4 more Smart Citations
“…Another population-based study also reported an increased risk with occupational exposure to herbicides (OR 3.06, 95% CI 1.34-7.00) [290]. A family-based study that found a dose-response relationship between overall pesticide exposure and PD reported an increased risk related to herbicides (OR 1.59, 95% CI 1.00-2.54) but could not examine dose-response [302].…”
Section: Case-control Studiesmentioning
confidence: 97%
“…In most studies of pesticides in relation to PD exposure was assessed retrospectively as a broad category, rather than examining specific substances. Of 38 case-control studies, 19 reported increased risk of PD [147,154,156,[289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] with ORs ranging between 1.3 and 3.7 for most studies. One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301].…”
Section: Case-control Studiesmentioning
confidence: 99%
See 3 more Smart Citations